The impact of steam on the electronic structure of the selective propane oxidation catalyst MoVTeNb oxide (orthorhombic M1 phase). Issue 14 (9th March 2015) - Heine, Christian; Hävecker, Michael; Trunschke, Annette; Schlögl, Robert; Eichelbaum, Maik
Abstract : Steam modifies the surface structure of the propane oxidation catalyst MoVTeNbO x and increases the selectivity to the product acrylic acid. Abstract : The selective propane oxidation catalyst MoVTeNb oxide M1 was investigated by microwave conductivity, synchrotron X-ray photoelectron, soft X-ray absorption and resonant photoelectron spectroscopy under reaction conditions to identify the influence of steam on the electronic bulk and surface properties. Steam significantly increases both the conversion of propane and the selectivity to the target product acrylic acid. The increased catalytic performance comes along with a decreased conductivity, a modification of the surface chemical and electronic structure with an enrichment of covalently bonded V 5+ species to the extent of Mo 6+, a decreased work function and hence polarity of the surface and a modified valence band structure. The higher degree of covalency in metal oxide bonds affects the mobility of the free charge carriers, and hence explains the decrease of the conductivity with steam. Furthermore we could prove that a subsurface space charge region depleted in electrons and thus an upward bending of the electronic band structure are induced by the reaction mixture, which is however not dependent on the steam content.